2013
DOI: 10.1002/ijc.27910
|View full text |Cite
|
Sign up to set email alerts
|

KRAS G>A mutation favors poor tumor differentiation but may not be associated with prognosis in patients with curatively resected duodenal adenocarcinoma

Abstract: KRAS mutations have been found in duodenal adenocarcinomas and may have prognostic significance. The purpose of this study was to classify clinicopathological characteristics, microsatellite instability, and KRAS mutations and identify possible prognostic role of KRAS mutations in duodenal adenocarcinomas. Demographics, tumor characteristics and survival were recorded for 78 patients with duodenal adenocarcinomas (stages I to III). KRAS mutations were detected in 27 (34.6%) cases, of which the majority (74.1%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Previous studies from Japan with homogeneous ethnic groups showed a wide range of frequencies of KRAS mutation (9-71%), [13][14][15]19 and other studies with heterogeneous ethnic groups, such as studies from USA, also reported various frequencies of KRAS mutation (14-83%). 10,17,18,20 Various KRAS mutation frequencies in the previous studies may be related with different detection methods rather than diverse ethnic background. Several different techniques for detecting KRAS and/or BRAF mutation were used, including restriction fragment length polymorphism, allele-specific oligonucleotide hybridization, PCR-single-strand conformation polymorphism, allele discrimination assay and Sanger sequencing.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Previous studies from Japan with homogeneous ethnic groups showed a wide range of frequencies of KRAS mutation (9-71%), [13][14][15]19 and other studies with heterogeneous ethnic groups, such as studies from USA, also reported various frequencies of KRAS mutation (14-83%). 10,17,18,20 Various KRAS mutation frequencies in the previous studies may be related with different detection methods rather than diverse ethnic background. Several different techniques for detecting KRAS and/or BRAF mutation were used, including restriction fragment length polymorphism, allele-specific oligonucleotide hybridization, PCR-single-strand conformation polymorphism, allele discrimination assay and Sanger sequencing.…”
Section: Discussionmentioning
confidence: 91%
“…Although a few previous studies of small intestinal adenocarcinomas have examined KRAS and/or BRAF mutations, which are well-known oncogenes in colorectal cancer, most of these analyses were performed on small numbers of patients (Table 9). 1,3,[10][11][12][13][14][15][16][17][18][19][20] The frequency of KRAS mutations among small intestinal adenocarcinomas ranged from 9 to 83% in the previous studies. Previous studies from Japan with homogeneous ethnic groups showed a wide range of frequencies of KRAS mutation (9-71%), [13][14][15]19 and other studies with heterogeneous ethnic groups, such as studies from USA, also reported various frequencies of KRAS mutation (14-83%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations